Mega Coronary Arteries with Obstructive Coronary Artery Disease in Hypertrophic Obstructive Cardiomyopathy: A Case Report and Literature Review - Debasish Das; Debasis Acharya; Tutan Das; Subhas Pramanik (Journal of the Indian Academy of Echocardiography & Cardiovascular Imaging, 2022)
We report a rare case of hypertrophic obstructive cardiomyopathy (HOCM) presenting with mega coronary arteries with obstructive coronary artery disease. Interestingly, the patient had large septals, large diagonals, large obtuse marginal with a large left atrial branch, and a large conus almost mimicking a duplicate right coronary artery. Because of massive left ventricular hypertrophy, to overcome the supply-demand mismatch, coronary arteries may become large or with more arborization in hypertrophic cardiomyopathy but the same is rarely encountered in routine clinical practice. Our case is a rare illustration of the simultaneous presence of mega coronary arteries and critical obstructive coronary artery disease in HOCM in a young male of 38 years of age.